SÍNTESE E CARACTERIZAÇÃO DE NANOCOMPÓSITOS HIDROXIAPATITAGELATINA OBTIDOS PELO MÉTODO DE PRECIPITAÇÃO UTILIZANDO O MÉTODO DE RIETVELD E IVTF - Angelo, Liliam Cristina (2008)
Nano-structured hydroxyapatite with crystallinity and composition similar to bone apatite has been widely investigated in last years.Because the bone is a tissue that requires some degree of mechanics tension to keep its vitality, has been used some biopolymers, as the composite HAP/gelatin, in order to minimize this problem. This biomolecule shows a singular characteristic, once that is the main mineral and organic phase bone constituent, respectively. The objective of this work was to consider a route of synthesis in which the hydroxylapatite was gotten by precipitation reaction directly on the collagen and to check out the effect of the gelatin addition in the hydroxylapatite crystal structure. The synthesis used was the wet precipitation through the dripping of a solution contends H3PO4 on the Ca(OH)2 together the addition of gelatin solutions with different concentrations (3 and 4 g/L, named GEL1 and GEL2 respectively). Temperature of the synthesis was controlled in approximately 42oC and pH after the ending of the dripping was kept in 12. After the periods of 1 and 21 days of aging the samples had been characterized. The DRX analyses had shown that the samples with gelatin addition shows bigger unit cell volumes in the two periods of aging studied, when related with the samples controll. Samples (GEL2) shows lesser volumes that samples GEL1, which had the biggest interactions occured between íons Ca2+ of the HAP and íons R___COO- of the gelatin. With the calcite, CaCO3, formation as second phase for these samples, íons Ca2+ are removed of the HAP structure, originating a calcium defficient HAP, and this, probably, makes with that the unit cell volumn diminishes. However, in the thermally treated samples, a unit cell volumn reduction more significant occurs to sample controll (AC) and GEL1, when the samples are aging for more time. For the samples did not treat thermally; it was observed in the same time of aging (21 days), the unit cell volume also is lesser must mainly by the decomposition. mainly the decomposition of carbonate apatites in CaO. On the microstrains of the crystal, were observed that when crystallite size increases there is a consequent microstrains reduction due to reduction of the internal tensions in the crystal while it grows. The FTIR analysis shows that type B carbonate apatite occurs, due the groups PO4 3- are substituted by groups CO3 2-. The substitution was more evident in the controll samples (AC) and GEL1 with lesser aging time, in samples GEL2, the phosphate bands are more evidentes. The SEM (scanning electro microscopy) micrographs show that there are formation of agglomerates and that the crystals are nano-structured. These results confirm that the gelatin presence affects directly the HAP structural properties. The method of synthesis presented in this study is a useful tool to production of nano crystals of the apatites structurally mimicking biological apatite.